Gold: An Investment Option (Trinity Journal of Management, IT & Media (TJMITM), 2010)
During these tough economic times,  many investors are starting to panic.  Since many of these investors are  putting their life savings on the line,  they want their investments to be  safe and smart, yielding positive  results both now and in the future.  They have lost trust in the stock  market and have no idea where to  invest their money. In the face of such unsure times,  there is a sound solution: invest your  money in gold and other precious  metals. According to NB/ (National  Bullion Investors, LLC), "Gold  prices will rise next year as the financial crisis pushes more  investors into the precious metal safe  haven". For the past ten years, Alan  Greenspan, the widely respected  former chairman of the US Federal  Reserve, has touted the wisdom of investing in gold. He predicted that  fiat money would someday be  worthless but commented that, "Gold  is always accepted. "
Keywords: National Bullion Investors, LLC; Federal Reserve